The development of mobile learning media using computer-aided manufacturing simulation in computer numerical control lathe - Rahdiyanta, Dwi; Wijanarka, Bernadus Sentot; Sandy, Kurnia; Agustiningsih, Rini; Pratiwi, Henny (AIP conference proceedings, 2023)
This research aims to produce products in the form of lathe computer numerical control (CNC) learning media in non-conventional machining engineering subjects at Vocational High School 2 Klaten. This research is a Research and Development research based on ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The product was tested on 67 students majoring in Metal Fabrication and Manufacturing Engineering. Data is collected using questionnaires and data analysis using descriptive analysis techniques. The results obtained that android-based learning media developed showed positive results, including from material experts got a percentage of 91.1%, media experts 94.5%, from teachers 94.7% and student responses 77.9%. With these results it can be concluded that the learning media is feasible to be used for the learning of CNC machining lathes.